Redescription of a forgotten nudibranch Miamira striata (Eliot, 1904) and review of the taxonomic status of the genus Orodoris (Nudibranchia: Chromodorididae: Miamirinae) - Tibiriçá, Yara; Gosliner, Terrence M.; Bonomo, Lynn J.; Cervera, Juan Lucas (Zootaxa, 2021)
The genus Orodoris Bergh, 1875 is a small genus that together with Miamira Bergh, 1875, was considered as a junior synonym of Ceratosoma A. Adams & Reeve, 1850. This decision was based on a morphological phylogenetic study conducted in 1999 that recovered the monophyly of the Ceratosoma. However, in 2012, molecular evidences led to the resurrection of Miamira, while Orodoris was retained as a junior synonym of Miamira with no further details. Here we revise the status of the genus Orodoris in light of the rediscovery of M. striata (syn. Orodoris striata Eliot, 1904). Our phylogenetic analysis revealed a close sister relationship between Miamira striata and Miamira miamirana Bergh, 1875 which nested within the Miamira clade. Therefore, to retain the monophyly of Miamira, the genus Orodoris should be maintained as a junior synonym of the former. This study proposes a neotype for M. striata and underscores the importance of reviewing historical taxonomic changes and investigating ancient descriptions prior to describing new taxa. Our study also confirms that Miamira magnifica Eliot, 1910 from the Indian Ocean and Miamira flavicostata Baba, 1940 from the Pacific Ocean represent two distinct, sister species.